2011
DOI: 10.1108/02580541111103891
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable leadership

Abstract: PurposeReviews the latest management developments across the globe and pinpoints practical implications from cutting‐edge research and case studies.Design/methodology/approachThis briefing is prepared by an independent writer who adds their own impartial comments and places the articles in contextFindingsGood leadership is the key to success in almost any human enterprise requiring cooperation and team working in order to realize a common goal. This is true whether the discussion is about business, industry, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Furthermore, a recently conducted survey by the United Nations Global Compact & Accenture (2010) of a thousand CEOs from over 100 countries showed that many current managers and leaders are lacking sustainability skills, which are required for the future success of businesses (Lacy, Haines & Hayward, 2012). The findings are in tune with the ideas of Anonymous (2011) andLacy, Haines &Hayward (2012), who wrote that the mind-sets and views about successful leadership have to change in order to embrace the concept of SD across all industries, whether in science, business, education, or government. In support to the above ideas, it has been identified in the UK Government Growth Review that only effective and responsible leadership can help to achieve a sustainable economy (Department for Business Innovation & Skills [BIS], 2012).…”
Section: Sustainable Development and Lack Of Sustainable Leaderssupporting
confidence: 70%
“…Furthermore, a recently conducted survey by the United Nations Global Compact & Accenture (2010) of a thousand CEOs from over 100 countries showed that many current managers and leaders are lacking sustainability skills, which are required for the future success of businesses (Lacy, Haines & Hayward, 2012). The findings are in tune with the ideas of Anonymous (2011) andLacy, Haines &Hayward (2012), who wrote that the mind-sets and views about successful leadership have to change in order to embrace the concept of SD across all industries, whether in science, business, education, or government. In support to the above ideas, it has been identified in the UK Government Growth Review that only effective and responsible leadership can help to achieve a sustainable economy (Department for Business Innovation & Skills [BIS], 2012).…”
Section: Sustainable Development and Lack Of Sustainable Leaderssupporting
confidence: 70%